A survey on andragogy principles for web based instruction in Malaysia higher education - Tasir, Zaidatun; Aris, Baharuddin; Ali, Mohamad Bilal; Harun, Jamalludin; Md. Noor, Norah; Mohd. Said, Mohd. Nihra Haruzuan (Faculty of Education, 2009)
Universitys lecturers need to focus on learning theory in the design of instruction so that they can create lessons that are not only technology effectiveness but also are meaningful from the learners perspectives. The appropriate learning theory that web-based developers should consider in designing web-based learning for universitys students is Andragogy since it describes the approach based on self directed learning theory. This research reports on a research project that investigated the andragogical assumptions preferred by pre-service teachers in Malaysia for online learning. Andragogical assumptions by Knowles (1984) are based on six aspects, which are Learners need to know, Learners self concept, Role of learners' experience, Readiness to learn, Learning Orientation, and Motivation to learn. To gather the data, questionnaires were distributed among 432 pre-service teachers in three educational institutions in Malaysia and descriptive analyses have been conducted. Samples of this study were selected using cluster randomized sampling technique. The findings showed that majority of the pre-service teachers in this study agreed on four Andragogical Assumptions, which were Learners need to know, Readiness to learn, Learning Orientation, and Motivation to learn. However, they were somewhat agreed on the other two assumptions; Learners self concept and Role of learners' experience. In terms of web-based design elements, most of the respondents agreed on the principles of information and interaction design. Though they somewhat agreed on the interface design of web-based instruction. The findings have implications for educators involved in designing online learning applications. They have to consider such student preference when planning teaching and learning activities.